Pesan Dakwah dan Toleransi pada Serial Indonesia Rumah Bersama dalam Channel Jeda Nulis - Nataniel, Riki; Kustiawan, Winda; Bahri, Andini Nur (Lembaga Yasin AlSys, 2023)
The purpose of this study is to find out what da'wah messages are contained in the content of the Indonesia Rumah Bersama series and to find out the message of tolerance that is dominant in the Indonesian Rumah Bersama series by Habib Ja'far. The method used in this study is a qualitative research method by analyzing da'wah messages that contain tolerance in the content of the Indonesia Rumah Bersama series by Habib Ja'far which is in accordance with this research and with the coding sheet technique. Then. The technique in analyzing the data used is descriptive analysis which describes in detail the problems. The results of the research found are: Da'wah messages in the nine Indonesian video series Rumah Bersama by Habib Ja'far are beliefs including the purpose of worship, the key to heaven, the importance of religion in life, about divinity, and the urgency of literacy. Messages of preaching morals include controlling lust, guarding the mouth and hands, the best human being is that which is beneficial to other humans, cleansing oneself from all dirt and manners before going to bed. And the message of sharia da'wah includes setting one syawal, the essence of Eid al-Fitr, the essence of Eid al-Fitr, working is worship, consuming good food, following the times and orders to preach. The contents of the messages of tolerance in the nine Indonesian video series The joint house by Habib Ja'far based on Abdullah Hadziq's theory are acknowledging the rights of others, respecting the beliefs of others, agreeing in disagreement, and understanding each other.